المقاومة في الفن والمقاومة بالفن - أحمد, عزت (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
المقاومة في الفن والمقاومة بالفن كلتاهما ممارسة جماليَّة، وليست هذه نقطة الاشتراك الوحيدة فثمة نقاط التقاء أُخْرَى كثيرة، ولكن في مقابل ذلك هناك نقاط افتراق وتضادٍّ أحياناً، ونقاط الالتقاء والاختلاف هي ما تشكل هويَّة كلٍّ منهما وخصائصها. وعلى الرَّغْمِ من ذلك هناك الكثيرون الذين يخلطون بَيْنَ المفهومين. إنَّ التَّمييز بينهما والتفصيل في خصائصهما أمر مهمٌّ لأكثر من سبب، ومفيد على أكثر من مستوى وصعيد. رُبَّما يكون ضبط الاصطلاح والمفهوم هو الأكثر أهميَّة لأنَّهُ نقطة الأساس والانطلاق لأي علم. ذلك أنَّ وضوح المفاهيم والاصطلاحات هو مفتاح الفهم الصحيح، والتوظيف الصحيح والمفيد، والاستثمار الأكثر فائدة والأكثر سرعة، وإِلَى جانب ذلك يمكِّننا هذا التحديد من الابتعاد عن اللَّبْسِ الخلط والجدل العقيم ويضمن لنا توظيف وقتنا على نحو أفضل وأكثر استثماراً... المقاومة في الفن عامَّةً هي تصوير مقاومةٍ ما أو أكثر تصويراً فَقَطْ في فنٍّ من الفنون. تختلف طريقة التصوير وخصائصها تبعاً للمقاومة المصورة والفن الذي تُصوَّر فيه والفنان المبدع ذاته. ولذلك تتفاوت قدرات الفنون؛ شعر، قصة، رسم... على تصوير المقاومة تبعاً لأدوات الفن ومـهارة الفنان في استخدامها. أما المقاومة بالفن فهي مسعى لتحويل الفن ذاته إلى حالة من حالات المقاومة، فالفنان هنا لا يريد تصوير المقاومة في فنه وإنما يريد أن يجعل الفنَّ سلاحاً يقاوم به الموضوع المرفوض بالنسبة له. هذا الموضوع قد يكون احتلالاً، عدواناً، ممارسة اجتماعية خاطئة... على الرغم من هذه الفروق بينهما فإنهما يشتركان ببعض الخصائص والنقاط تجعل كل منهما يقوم بالدورين معاً، أو يرجح أحدهما على الآخر، ويمكن أن يحدث الخلط بينهما أحياناً. وهذا كله في حقيقة الأمر ما أردنا تبيناه والتفصيل به قدر الإمكان في بحثنا. Resistance in art and resistance by art are both a kind of an aesthetic action. This is not the only interference point, but there are other meeting points. On the other hand, there are sometimes points of a separation and a contradiction. Points of meeting and difference constitute the identity merit and feature for them. Distinguishing between them and elaborating their features are very important for many reasons, and are useful at many levels. Capturing the term and the notion would be most important. The clarity of terms and notions are the key concept for a clear understanding, correct and useful employment, a most useful and rapid investment. In addition to that, this specification allows me to avoid confusion and futile argument and allows us to employ our time in a better manner. Resistance in art is generally a portrait of one or more form of resistance in an art. The way of portraying, in addition to its qualities, differ according to the portrayed resistance, the art, and the artist. Accordingly, the kind of arts varies in portraying the resistance according to the instruments of art and the skillfulness of the artist using them. Regarding resistance by art, it is an aim to change art to kind of resistance. The artist here does not want to portray the resistance in his art, but he wants to make art a weapon through which he resists the subject he denies. These subjects may be colonization, occupation, or an unaccepted social behavior. In spite of all these differences between the two kinds, they both share some qualities and points. These similarities make both do the two roles simultaneously, or even to make one of them more possible than the other. However, it is possible some times the two might get mixes. This is in fact what I aimed in my research.